Intra-Household Gender Wage Gap in China: Evidence from the China Health & Nutrition Survey - Zhao, Zixin; Han, Ai; Wang, Shouyang (Asian Economic and Financial Review, 2022)
This paper analyzes the intra-household wage gap and wage determination of husbands and wives under the urban-rural dual economic structure in China. A two-step estimation procedure was used to determine the factors that are related to living in urban or rural areas by employing the probit model. Additionally, the effects of different factors affecting gender wage across regimes and between husbands and wives was examined using the seemingly unrelated regression estimation (SURE) model. It was found that the intra-household gender wage gap is larger in rural areas than in urban areas. At different percentiles, the gender wage gap is also different. There is a larger gender wage gap between low income earners than higher income earners. The largest gender wage gap is in the 10th percentile in rural areas with a wife–husband wage ratio of 67%. The wage determination pattern between spouses is different in urban and rural areas. Except for human capital impact, urban-rural dual economic structure and family factors, spousal factors also effect the intra-household wage gap.